Adaptation of the subtle and overt psychological abuse of women scale in clinical and community samples - Buesa, Sara; Calvete, Esther (Anales de Psicología / Annals of Psychology, 2011)
Psychological abuse against women by an intimate partner can take many modalities, including forms of overt and subtle abuse. The objectives of this research were to adapt the Subtle and Overt Psychological Abuse of Women Scale-SOPAS (Marshall, 2000) to Spanish women, and to study some of its psychometric properties, as well as to examine its association with other types of abuse and with the symptoms shown by victims of domestic violence. The study was carried out with two samples: a sample of 186 women from the community and a sample of 157 women victims of domestic violence. The results supported a one-dimension structure for the SOPAS, which was invariant for both samples. The SOPAS presented high internal consistency. The sample of victims scored much higher in subtle abuse than women in the community. Subtle abuse was associated more strongly with depression and post-traumatic stress than other measures of psychological abuse used in the study. The findings suggest that subtle abuse is a distinct form of abuse, which is different from overt forms of psychological abuse and has a significant impact on the victims’ mental health.